O jornalismo nas narrativas das crônicas de Rachel de Queiroz e Maria Judite de Carvalho - Moura, Ranielle Leal (2018)
The present thesis aims to understand, if and how, Rachel de Queiroz and Maria Judite de Carvalho in their narratives of the published chronicles, respectively, in the magazine O Cruzeiro and in the Diário de Lisboa, used values and characteristics that composse the journalistic ethos modern, created to the information field. The analytic inspiration has a theoretical-philosophical basis in hermeneutics and, therefore, intends to interpret the narratives of the columns of both journalists, having as a parameter Hermeneutic Circle of Paul Ricoeur (2010) from this author’s Action and Interpretation’s Theory, which structures of pre-figuration, configuration and refiguration of the narrated actions, gain projection in the way of narrating the world in its time. The intention is to perceive through the interpretation chronicles’ narratives published in “Última Página” e “Rectângulos da Vida”, traces that can evidence journalism model forged in modernity regime of historicity, considering the journalists mentioned were also writers and, therefore, associate to the literary field where the chronicle, this investigation’s object, has different characteristics. The study, after the interpretative process, proves the thesis that the analyzed narratives reveal a great absorption of values associated to the way of being of modern journalism.